Search for doubly charged Higgs boson production in multi-lepton final states using 139 fb$$^{-1}$$ -1 of proton-proton collisions at $$\sqrt{s}$$ s = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Springer Open.